Antenatal care for healthy pregnant women: a mapping of interventions from existing guidelines to inform the development of new WHO guidance on antenatal care. (23rd December 2015) - Abalos, E; Chamillard, M; Diaz, V; Tuncalp, Ӧ; Gülmezoglu, AM
Abstract : Background: The World Health Organization (WHO) is in the process of updating antenatal care (ANC) guidelines. Objectives: To map the existing clinical practice guidelines related to routine ANC for healthy women and to summarise all practices considered during routine ANC. Search strategy: A systematic search in four databases for all clinical practice guidelines published after January 2000. Selection criteria: Two researchers independently assessed the list of potentially eligible publications. Data collection and analysis: Information on scope of the guideline, type of practice, associated gestational age, recommendation type and the source of evidence were mapped. Main results: Of 1866 references, we identified 85 guidelines focusing on the ANC period: 15 pertaining to routine ANC and 70 pertaining to specific situations. A total of 135 interventions from routine ANC guidelines were extracted, and categorised as clinical interventions ( n = 80), screening/diagnostic procedures ( n = 47) and health systems related ( n = 8). Screening interventions, (syphilis, anaemia) were the most common practices. Within the 70 specific situation guidelines, 102 recommendations were identified. Overall, for 33 (out of 171) interventions there were conflicting recommendations provided by the different guidelines. Conclusion: Mapping the current guidelines including practices related to routine ANC informed the scoping phase for the WHO guideline for ANC. Our analysis indicates that guideline development processes may lead to different recommendations, due to context, evidence base or assessment of evidence. It would be useful for guideline developers to map and refer to other similar guidelines and, where relevant, explore the discrepancies in recommendations and others. Tweetable abstract: We identified existing ANC guidelines and mapped scope, practices, recommendations and source of evidence. Tweetable abstract: We identified existing ANC guidelines and mapped scope, practices, recommendations and source of evidence.